Occupational asthma in teachers. (13th September 2022) - Burge, S; Moore, V; Burge, C; Robertson, A; Huntley, C; Walters, G
Abstract: Background: Work-related asthma symptoms are common in teachers and teaching assistants, there are few studies evaluating their causes. Aims: To identify causes of occupational asthma in teachers and teaching assistants referred to the Birmingham Occupational Lung Disease clinic 2000–20 using evaluation of serial Peak Expiratory Flow (PEF) records. Methods: Teachers and teaching assistants with possible occupational asthma were asked to record PEF 2-hourly at home and work for 4 weeks. Their records were evaluated with the Oasys programme. Those with a positive score for any of the three scores (area between curves (ABC), timepoint and Oasys score from discriminant analysis) were included. Repeat records were made as indicated to help identify the cause and the effects of remedial actions. Results: Thirty-eight teachers or teaching assistants met the inclusion criteria with all three Oasys scores positive in 24, 2/3 scores in nine and 1/3 in five. The building was the likely cause in 17 (in new builds particularly acrylates from carpet adhesives and in old buildings mould and construction dust), bystander exposure to agents in the schools in 12 (cleaning agents, acrylates from photocopiers and chloramines from indoor pools) and materials used in the classroom in 9 (most commonly MDF in design and technology classes). We illustrate how the PEF records helped identify the cause. Conclusions: Oasys analysis of PEF records is a useful method of evaluating occupational asthma in teachers and identified difficult to confirm causes where successful remediation or redeployment was achieved. Abstract : Teachers may get occupational asthma from their school buildings, their cleaning or materials used in the classroom. Objective diagnoses can be made by Oasys analysis of serial peak flow records kept by the teacher which can identify the early disease and successful remediation. Identifying the cause of occupational asthma reduces the risks of job loss and unemployment.